Cardiac AAV9-S100A1 gene therapy rescues post-ischemic heart failure in a preclinical large animal model - Pleger, Sven Torsten; Shan, Changguang; Ksienzyk, Jan; Bekeredjian, Raffi; Boekstegers, Peter; Hinkel, Rabea; Schinkel, Stefanie; Leuchs, Barbara; Ludwig, Jochen; Qiu, Gang; Weber, Christophe; Raake, Philip; et al. (Science translational medicine, 2011)
As a prerequisite for clinical application, we determined the long-term therapeutic effectiveness and safety of adeno-associated virus (AAV)-S100A1 gene therapy in a preclinical large animal model of heart failure. S100A1, a positive inotropic regulator of myocardial contractility, becomes depleted in failing cardiomyocytes in humans and animals, and myocardial-targeted S100A1 gene transfer rescues cardiac contractile function by restoring sarcoplasmic reticulum calcium (Ca(2+)) handling in acutely and chronically failing hearts in small animal models. We induced heart failure in domestic pigs by balloon occlusion of the left circumflex coronary artery, resulting in myocardial infarction. After 2 weeks, when the pigs displayed significant left ventricular contractile dysfunction, we administered, by retrograde coronary venous delivery, AAV serotype 9 (AAV9)-S100A1 to the left ventricular, non-infarcted myocardium. AAV9-luciferase and saline treatment served as control. At 14 weeks, both control groups showed significantly decreased myocardial S100A1 protein expression along with progressive deterioration of cardiac performance and left ventricular remodeling. AAV9-S100A1 treatment prevented and reversed these functional and structural changes by restoring cardiac S100A1 protein levels. S100A1 treatment normalized cardiomyocyte Ca(2+) cycling, sarcoplasmic reticulum calcium handling, and energy homeostasis. Transgene expression was restricted to cardiac tissue, and extracardiac organ function was uncompromised. This translational study shows the preclinical feasibility of long-term therapeutic effectiveness of and a favorable safety profile for cardiac AAV9-S100A1 gene therapy in a preclinical model of heart failure. Our results present a strong rationale for a clinical trial of S100A1 gene therapy for human heart failure that could potentially complement current strategies to treat end-stage heart failure.